TI_GERICHTE 12.2021.42 vom 12. Juli 2021 , Società anonima - consultazione dei libri e della corrispondenza - rifiuto - TI Tribunale d'appello (2021)
Società anonima - consultazione dei libri e della corrispondenza - rifiuto